By the horns - Dixon, Ruby, 1976- (Dixon, Ruby, 1976- Royal Artifactual Guild, 2025)
"In a world of magical artifacts and fantastical beings, a woman with a deadly magic secret needs the help of the minotaur she's trying to forget in the sizzling sequel of New York Times bestselling author Ruby Dixon's new steamy monster romance series. Gwenna has always considered herself a normal person. A former servant, she wants nothing more than to land a steady job with the Royal Artifactual Guild so she can make some steady coin to send home to her mother. She's not special. She's certainly not a necromancer. That would be impossible, given how necromancing (or any 'mancing) is forbidden upon penalty of death. So if the dead keep talking to her? Well, she's going to keep on ignoring them. They're not going to stand in the way of her dreams. Also standing in her way? One big, arrogant, far-too-flirty Taurian named Raptor. They slept together once, and now he wants more . . . but she doesn't have time for that. Her focus is on being a fledgling, a trainee for the Royal Artifactual Guild. But Raptor won't go away. He's on a secret mission for the guild to find an artifact thief. Problem is, he thinks the thief is Gwenna. How can she convince Raptor that he's got the wrong girl when all the signs point to her? And how do you tell a Taurian you can't date him because you hear dead people and it might cost you your life?"--